Analisis Faktor yang Mempengaruhi Perilaku Masyarakat untuk Berpartisipasi dalam Program Citarum Harum - Aulia Hadining; Kusnadi; Gina Lova Sari; Hadi Sudarjat (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
The behavior of people who depend on the Citarum River Watershed (DAS Citarum) in disposing of waste has a direct impact on the damage and pollution experienced by the Citarum River. Therefore, the Citarum Harum program by the government is expected to change the Citarum River Watershed (DAS Citarum) community more importantly in terms of waste management. The purpose of this study is to determine the factors that influence the behavioral intention of the Citarum watershed community to realize the Citarum Harum. This research was conducted by surveying through questionnaires to 170 respondents. After collecting data, the data then processed using Partial Least Square (PLS) method with SmartPLS 3.0 software. The results of this study indicate that the Perceived Behavioral Control (PBC), Incentive Measure (IM), and Personal Norm (PN) factors significantly influence the Behavioral Intention (BI) respectively amount 16.3%, 15.9%, and 19.1%. While the Knowledge Theory (ETK) and Environmental Practices Knowledge factors influence the Attitude Towards Behavior (ATT) to understand in actualize citarum harum program respectively amount 38.4% and 21.7%.